GAMBARAN INTERAKSI SOSIAL LANSIA DI MASYARAKAT - Suparniyati Suparniyati; Bayhakki Bayhakki; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
The last stage of the human life is elderly signed with some physical and psychocosocial changes. The main social problem that occurs in almost all elderly is the decrease in social interaction. This study aimed to analyze social interactions that occur in the elderly who live in the community. This study used descriptive research design with cross sectional approach. The sample of this study were 100 respondents taken based on inclusion criteria using purposive sampling technique. The results showed the majority of research subjects aged 60-74 years old (97%), female (78%), moslems (95%), ethnic Minang (40%), married (49%), graduated from high school (45%). Most of the elderly were retired (48%), and the majority of elderly people have a history of DM (27%). Descriptive test results show the social interaction of the elderly were medium category (84%). Elderly social interaction with family showed moderate (73%), social interaction of the elderly with neighbors showed moderate (54%), social interaction with the community showed moderate (81%), and social interaction of the elderly with fellow elderly with moderate (83%). It is expected that the health center can mobilize every Posbindu to regularly review the social interactions of the elderly in the community and for nurses in providing health promotion about the benefits of social interaction in the elderly in the community. Keywords: community, elderly, social interactions